Development of metal mountable RFID tag antenna in ultra high frequency range / Najwa Mohd Faudzi - Mohd Faudzi, Najwa (2015)
In recent years, Radio Frequency Identification (RFID) technology is highly demanded in various applications, requiring a rapid development in the RFID technology. The performance o f the RFID system mainly depends on the RFID tag, as the tag will be attached on the items or objects that need to be identified. The research described in this thesis focuses on the development of the tag antenna designs to meet the requirements o f certain applications which are small size and insensitive to metal object. In this project, three designs o f UHF-RFID tag antenna were proposed; namely a compact dipole tag antenna, metal mountable meander feed line tag antenna and metal mountable ladder feed line tag antenna. The Design 1 tag antenna has obtained a size reduction o f 70% from the straight half wavelength dipole antenna through the implementation of two miniaturization methods, which are meandering and capacitive tip-loading. However, high sensitivity of the tag to the metal objects attached leads to the formation of the Design 2 tag antenna, which included a ground plane in the antenna structure. The Design 2 tag antenna was then improved to the Design 3 tag antenna, which has smaller size and better reading range, through the implementation of capacitive tip-loading structure and ladder feed line respectively. In order to easily match the impedance o f the antenna with the chip, a T-matching technique has been inserted in all three tag antenna designs. The simulation process was carried out using CST Studio Suite software, while the measurement of S n , antenna impedance and reading range was done using fabricated jig, Image method, Vector Network Analyzer and RFID reader. From measurement, the Design 1 tag antenna has achieved the longest reading range in free air with the value o f 9.6 in, but failed to be detected when attached on metal object. In contrast, Design 2 and Design 3 tag antennas can be detected in both conditions with the read range value of 2.2 m and 2.3 m in free air, while on metal object the read range is 2.0 m and 2.2 m respectively.